Medication approaches potentially inappropriate for the elderly: a Cuban proposal - Irma Leonor Ortega López; Clemente Couso Seoane; Niurka María Dupotey Varela; Ivette Reyes Hernández (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: The impact of inappropriate prescription of medication in the elderly has led to the development of methods for its reduction in several parts of the world. Objective: To design and validate the medication approaches potentially inappropriate in the elderly, adapted to the socio-sanitary environment of Cuba. Methods: A qualitative investigation was carried out, in which the approaches were validated by means of the Delphi methodology, by an experts committee (specialists in geriatrics medicine and clinic from different geographical areas of the country), and the internal consistency was calculated by means of the alpha coefficient of Cronbach. Results: The approaches were structured in three lists: 1) potentially inappropriate medication, advised medication non prescribed, when contraindication doesn't exist for its use; 2) medication potentially inappropriate, independent from the diagnosis or clinical condition; 3) potentially inappropriate medication, depending on the diagnosis or clinical condition. Conclusions: The validity of the content and the appropriate internal consistency of the designed approaches for the medication identification potentially inappropriate in the elderly were demonstrated.